Giant, unconventional anomalous Hall effect in the metallic frustrated magnet candidate, KV3Sb5 - Yang, Shuo-Ying; Wang, Yaojia; Ortiz, Brenden R; Liu, Defa; Gayles, Jacob; Derunova, Elena; Gonzalez-Hernandez, Rafael; Šmejkal, Libor; Chen, Yulin; Parkin, Stuart S P; Wilson, Stephen D; Toberer, Eric S; et al. (Science advances, 2020)
The anomalous Hall effect (AHE) is one of the most fundamental phenomena in physics. In the highly conductive regime, ferromagnetic metals have been the focus of past research. Here, we report a giant extrinsic AHE in KV3Sb5, an exfoliable, highly conductive semimetal with Dirac quasiparticles and a vanadium Kagome net. Even without report of long range magnetic order, the anomalous Hall conductivity reaches 15,507 Ω-1 cm-1 with an anomalous Hall ratio of ≈ 1.8%; an order of magnitude larger than Fe. Defying theoretical expectations, KV3Sb5 shows enhanced skew scattering that scales quadratically, not linearly, with the longitudinal conductivity, possibly arising from the combination of highly conductive Dirac quasiparticles with a frustrated magnetic sublattice. This allows the possibility of reaching an anomalous Hall angle of 90° in metals. This observation raises fundamental questions about AHEs and opens new frontiers for AHE and spin Hall effect exploration, particularly in metallic frustrated magnets.